(untitled) (Andamios, Revista de Investigación Social, 2011)
Summary: This article explores representation of violence in contemporary Mexico in three books by Sergio González Rodríguez. In his journalistic accounts as well as in other of his books, he approaches the homicides against women in Ciudad Juárez, the drug trafficking cartels and recent beheadings, in order to encompass a broader consideration of violence as a global phenomenon that exceeds Mexico. Thus his interdisciplinary analysis offers a model to rethink recent Mexican violence in relation to the crisis of the National State, its Judicial system, and its politics, vis-a vis processes of globalization. Key words: Narratives of violence, drug trafficking, demise of State, Women’ homicides, predatory logic.